Drug Repurposing: Deferasirox Inhibits the Anti-Apoptotic Activity of Mcl-1 - Bourafai-Aziez A; Benabderrahmane M; Paysant H; Weiswald LB; Poulain L; Carlier L; Ravault D; Jouanne M; Coadou G; Oulyadi H; Voisin-Chiret AS; Sopková-de Oliveira Santos J; et al. (Dove Medical Press, 2021)
Asma Bourafai-Aziez,1 Mohammed Benabderrahmane,2 Hippolyte Paysant,3,4 Louis-Bastien Weiswald,3,4 Laurent Poulain,3,4 Ludovic Carlier,5 Delphine Ravault,5 Marie Jouanne,2 Gaël Coadou,1 Hassan Oulyadi,1 Anne-Sophie Voisin-Chiret,2 Jana Sopková-de Oliveira Santos,2 Muriel Sebban1 1Normandie Université, UNIROUEN, INSA de Rouen, CNRS Laboratoire COBRA (UMR 6014 & FR 3038), Rouen, 76000, France; 2Normandie Univ, UNICAEN, CERMN, Caen, 14000, France; 3Normandie Université, UNICAEN, Inserm U1086 ANTICIPE «Interdisciplinary Research Unit for Cancer Prevention and Treatment», Biology and Innovative Therapeutics for Ovarian Cancers Group (BioTICLA), Centre de Lutte Contre le Cancer F. Baclesse, Caen, 14076, France; 4UNICANCER, Centre de Lutte Contre le Cancer F. Baclesse, Caen, 14076, France; 5Sorbonne Université, École Normale Supérieure, PSL University, CNRS, Laboratoire des Biomolécules, LBM, Paris, FranceCorrespondence: Muriel SebbanNormandie Université, UNIROUEN, INSA de Rouen, CNRS Laboratoire COBRA (UMR 6014 & FR 3038), Rouen, 76000, France, Tel +33 2 35 52 29 44Fax +33 2 35 52 24 41Email muriel.sebban@univ-rouen.frJana Sopková-de Oliveira SantosNormandie Univ, UNICAEN, CERMN, Caen, 14000, FranceTel +33 2 31 56 68 21Fax +33 2 31 56 68 03Email jana.sopkova@unicaen.frIntroduction: With the aim of repositioning commercially available drugs for the inhibition of the anti-apoptotic myeloid cell leukemia protein, Mcl-1, implied in various cancers, five molecules, highlighted from a published theoretical screening, were selected to experimentally validate their affinity toward Mcl-1.Results: A detailed NMR study revealed that only two of the five tested drugs, Torsemide and Deferasirox, interacted with Mcl-1. NMR data analysis allowed the complete characterization of the binding mode of both drugs to Mcl-1, including the estimation of their affinity for Mcl-1. Biological assays evidenced that the biological activity of Torsemide was lower as compared to the Deferasirox, which was able to efficiently and selectively inhibit the anti-apoptotic activity of Mcl-1. Finally, docking and molecular dynamics led to a 3D model for the Deferasirox:Mcl-1 complex and revealed the positioning of the drug in the Mcl-1 P2/P3 pockets as well as almost all synthetic Mcl-1 inhibitors. Interestingly, contrary to known synthetic Mcl-1 inhibitors which interact through Arg263, Deferasirox, establishes a salt bridge with Lys234.Conclusion: Deferasirox could be a potential candidate for drug repositioning as Mcl-1 inhibitor.Keywords: drug repurposing, Mcl-1, Deferasirox, NMR, docking, dynamics